Kate Chopin's private papers - Chopin, Kate, 1850-1904 (Indiana University Press, 1998)
"Kate Chopin, according to her contemporaries, was a "woman of mysterious fascination"--And Kate Chopin's Private Papers reveals many of the author's secrets. Chopin (1850-1904), author of about a hundred short stories and two novels (The Awakening and At Fault), also kept diaries, wrote letters and poems, translated short stories and articles from the French, and worried about her career. Chopin's newly discovered manuscripts, published for the first time here, reflect her dedication to revision and improving her craft; her manuscript account books show her meticulous control of her career and her pursuit of audiences. These papers illuminate the growth of Chopin as a writer, bring into focus the reactions of critics to her work, and settle a number of controversies in Chopin studies."--Jacket.